Using of DNA Fingerprinting in Poultry Research - Farrag, S.A.; Tanatarov, A.B.; Soltan, M.E. (International Journal of Poultry Science, 2010)
Genetic fingerprinting, DNA testing or DNA profiling is a technique to distinguish between individuals of the same species using only samples of their DNA. In modern animal breeding and production, with welfare and optimum nutrition, the major health problems arise mainly from genetic background. Obviously the selection does not affect the genome, but rather changes gene frequencies in the population and modifies the range of genetic variation of selected and correlated traits. These effects can be detected at the DNA level with the use of appropriate tools. DNA fingerprinting is a powerful tool in poultry for investigating genetic diversity within stocks and establishing relationships among stocks, characterizing individuals or populations genotypically, studying the relative contribution of evolutionary forces to genetic differences between populations, for marker assisted selection, to assist in gene introgression, to predict hybrid vigor and provide useful information for the pre-selection of populations to be used in crossbreeding. This review summarizes the use of genetic fingerprinting in poultry research, especially in some genetic resources of economically important species such as chickens, quails, ducks, goose, turkey and other poultry.